The Mondly Application as A Modern Solution for Improving Students Speaking Skills - Fitria Nasution, Khairika; Hz, Benni Ichsanda Rahman (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to explore the use of the Mondly app in improving students' English speaking skills and identify challenges that arise during its use. Using a descriptive qualitative approach, data were collected through open-ended questionnaires and semi-structured interviews with 30 high school students who actively use Mondly. Data analysis was conducted using thematic analysis techniques, through a process of coding, categorizing, and interpreting meaning based on themes that emerged from the data. The results show that Mondly positively contributes to the development of students' speaking skills through features such as speech recognition, conversation simulations, and real-time feedback. Gamification elements and personalized learning paths increase student motivation and engagement. Three main benefits identified were: (1) reduced speaking anxiety due to a pressure-free learning environment; (2) improved pronunciation, intonation, and sentence structure through repeated practice; and (3) increased confidence in speaking English in real-life situations. However, challenges identified include dependence on internet connection, inaccurate feedback, and limitations in creating spontaneous interactions. This study recommends the integration of AI-based technologies such as Mondly in language learning to effectively support the development of oral communication